Hubungan Perilaku Keluarga Dengan Kejadian Ispa Pada Balita Di Puskesmas Bangetayu Semarang - Anisa, Siti Nur Anisa; Indra Tri Astuti; Kurnia Wijayanti (An-Najat, 2025)
Acute Respiratory Infection (ARI) is one of the leading causes of death among toddlers. One of the triggers for ARI is family behavior. The aim of this study is to determine the relationship between family behavior and the incidence of ARI in toddlers at Bangetayu Health Center in Semarang. This study uses a quantitative correlational approach with a cross-sectional design. A total of 175 toddlers were selected through consecutive sampling. Bivariate analysis was performed using the Spearman's test. The results of this study showed that 80 respondents (47.7%) were parents aged 26-35 years, 152 respondents (86.9%) were female parents, 68 respondents (38.9%) had elementary school education, 75 respondents (42.9%) were traders, 165 respondents (94.4%) were of Javanese ethnicity, 171 respondents (97.7%) were Muslim, with an average toddler age of 2-3 years and an average weight of 14.54 kg. 107 respondents (61.1%) had male toddlers, 144 respondents (82.3%) had a birth weight of 2500 grams, 168 respondents (96.0%) consumed vitamin A, 156 respondents (89.1%) received age-appropriate immunizations, and 141 respondents (80.6%) practiced exclusive breastfeeding. The bivariate analysis using Spearman's test showed the following results: for smoking habits, ρ = 0.000 and r = 0.74; for using firewood for cooking, ρ = 0.008 and r = 0.199; for using mosquito coils, ρ = 0.002 and r = 0.232; for opening windows, ρ = 0.005 and r = 0.211; and for burning trash, ρ = 0.020 and r = 0.175. It can be concluded that there is a relationship between family behavior and the incidence of ARI in toddlers at Bangetayu Health Center in Semarang.